2017
DOI: 10.4274/turkderm.55265
|View full text |Cite
|
Sign up to set email alerts
|

The role of uric acid in metabolic syndrome in patients with psoriasis

Abstract: Background and Design:Psoriasis patients have increased risk of obesity, metabolic syndrome and cardiovascular disease. Uric acid is a metabolic marker associated with metabolic syndrome and cardiovascular diseases. Uric acid levels increase in psoriasis as well. The aim of this study was to investigate the role of uric acid in metabolic syndrome in patients with psoriasis. Materials and Methods: Chronic plaque psoriasis patients who presented to the dermatology outpatient clinics in a university-affiliated tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The mean age of patients was 40.89 years (range: 26.03-49.70 years) and that of healthy controls 39.64 years (range: 23.40-49.48 years). Thirteen studies were reported from Turkey [16][17][18][19][20][21][22][23][24][25][26][27][28], eight from Iran [11,[29][30][31][32][33][34][35], seven from India [36][37][38][39][40][41][42], five from Poland [5,[43][44][45][46], three from the USA [47][48][49], two from Spain [2,10], Japan [50,51], Egypt [52,53], and Italy [54,55], one from Austria [56], Romania [1], Portugal [57], Iraq [58], and China [59]. Th...…”
Section: Literature Searchmentioning
confidence: 99%
“…The mean age of patients was 40.89 years (range: 26.03-49.70 years) and that of healthy controls 39.64 years (range: 23.40-49.48 years). Thirteen studies were reported from Turkey [16][17][18][19][20][21][22][23][24][25][26][27][28], eight from Iran [11,[29][30][31][32][33][34][35], seven from India [36][37][38][39][40][41][42], five from Poland [5,[43][44][45][46], three from the USA [47][48][49], two from Spain [2,10], Japan [50,51], Egypt [52,53], and Italy [54,55], one from Austria [56], Romania [1], Portugal [57], Iraq [58], and China [59]. Th...…”
Section: Literature Searchmentioning
confidence: 99%